Modification and extension of the anaerobic model N°2 (AM2) for the simulation of anaerobic digestion of municipal solid waste - Amine Hajji; Younes Louartassi; Mohammed Garoum; Najma Laaroussi; Mohammed Rhachi (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
Anaerobic digestion is a complex process whose understanding, optimization, and development require mathematical modeling to simulate digesters' operation under various conditions. Consequently, the present work focuses on developing a new and improved model called